Effect of liquid product coverage on mass transfer and model development for gas-solid reaction in later reaction stage. (March 2022) - Liu, Ming; Shen, Zhongjie; Xu, Jianliang; Liang, Qinfeng; Liu, Haifeng
Highlights: In-situ gasification demonstrated the slag coverage on residual carbon. Molten slag on particle surface increase diffusion resistance of gasifying agent. Residual carbon was found both on particle surface and inside fine slag from gasifier. Critical point was found in the differential curve of reaction rate. Ash content and reactivity of coal char affect the critical carbon conversion. Abstract: The carbon conversion efficiency of coal is important performance index for gasifiers. Besides, the prediction of reaction rate of coal particle decides the operating residence time in gasifier. In this work, effect of molten slag covered on particle surface on mass transfer at high temperatures was investigated. In-situ gasification process of different char particles was analyzed and the molten slag enclosed residual carbon was found. The residual carbon inside fine slag and the core particle enclosed with slag from commercial entrained-flow gasifier were demonstrated. The carbon contents were up to 70% and 45% in gasification residual and fine slag. A critical point was found in the differential results of the reaction rate curve. The critical carbon conversion is about 0.93, 0.99 and 0.93 for three different coal chars. The reaction rates of different coal chars all showed linear decrease in the later reaction stage because of the diffusion resistance. Based on the reaction mode, the proposal of reaction model for carbon conversion prediction of high ash content coal chars in the later reaction stage was developed. The predicted carbon conversion of the proposed new model showed ideal agreement with the experimental data. This work introduced the formation of residual carbon in detail and supplies the new predictive reaction rate that considering ash fusion at high temperatures. Graphical abstract: Image, graphical abstract